Performance Analysis of Deep Neural Networks for Object Classification with Edge TPU - Asyraaf Jainuddin A.A.; Hou Y.C.; Baharuddin M.Z.; Yussof S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Benchmarking; Computer aided instruction; Deep neural networks; Image coding; Large dataset; Learning systems; Neural networks; Data transferring; Data-transmission speed; Hardware selection; Machine learning applications; Neural network model; Object classification; Performance analysis; Processing units; Deep learning